Assessment of the inhibitory effects of sodium nitrite, nisin, potassium sorbate, and sodium lactate on Staphylococcus aureus growth and staphylococcal enterotoxin A production in cooked pork sausage using a predictive growth model - Lu Lin; Jie Yun Hu; Yi Wu; Min Chen; Jie Ou; Wei Ling Yan (Food Science and Human Wellness)
This study was conducted to analyze the effects of sodium nitrite, nisin, potassium sorbate, and sodium lactate against Staphylococcus aureus (S. aureus) growth and staphylococcal enterotoxins (SEs) production in cooked pork sausage by inoculating sausage samples containing preservative with an S. aureus strain producing staphylococcal enterotoxin A (SEA) and then storing them at 37 °C for 36 h. Samples were analyzed every 3 h to count the S. aureus colonies and to detect SEA. The modified Gompertz model was used to describe S. aureus growth in the samples under various conditions, and the preservatives with a significant antimicrobial effect were selected. In addition, the antimicrobial effects of the selected preservatives under various concentrations were tested. Results showed that sodium nitrite, nisin, and potassium sorbate had a weak effect against S. aureus growth and had no effect against SEA production, whereas sodium lactate could significantly inhibit S. aureus growth and SEA production. Moreover, the antimicrobial effect of sodium lactate was concentration-dependent, wherein sodium lactate concentration <12 g/kg showed no inhibitory effect, but when the concentration was increased to 24 g/kg, sodium lactate could effectively inhibit S. aureus growth and SEA production, and at 48 g/kg, sodium lactate had a significant inhibitory effect. Keywords: Staphylococcus aureus, Staphylococcal enterotoxin A, Cooked pork sausage, Preservative, Sodium lactate